ТЕОРЕТИЧНІ АСПЕКТИ ВИЗНАЧЕННЯ СУТНОСТІ ПОНЯТТЯ «СОЦІАЛЬНА ЗРІЛІСТЬ» У ПСИХОЛОГІЧНИХ ДОСЛІДЖЕННЯХ - Школьна, Марія (Збірник наукових праць Уманського державного педагогічного університету, 2020)
У статті розглянуто концептуальні підходи щодо визначення сутності поняття «соціальна зрілість» у психологічних дослідженнях. Визначено, що вітчизняні психологи розглядають поняття «соціальна зрілість» з точки зору значущості до суспільства. Теоретичний аналіз психологічних досліджень дозволяє стверджувати, що дослідники зосереджують увагу на наступних соціальних якостях особистості, як-от: соціальна активність, соціальна відповідальність, солідарність, толерантність, самостійність, незалежність. В статье рассматриваются концептуальные подходы к определению понятия «социальная зрелость» в психологических исследованиях. Установлено, что отечественные психологи рассматривают понятие «социальная зрелость» с точки зрения полезности для общества. Теоретический анализ психологических исследований позволяет утверждать, что психологи концентрируют внимание на таких социальных качествах, как: социальная активность, социальная ответственность, солидарность, толерантность, самостоятельность, независимость. The article is conceptual approaches to defining the essence for the concept of «social maturity». Determined that our scientists considered the concept of «social maturity» in terms of importance to society. Theoretical analysis of psychologica lresearch suggests that researchers focusing on the social personality traits, suchas: social activity, social responsibility, solidarity, tolerance, autonomy and independence. The analysis of western psychological theories are given the reason to believ that self-socially mature person is characterized by self-realization, self-actualization, self-improvement (in the autonomy of social norms and prohibitions); the discovery of their own individuality, uniqueness (A. Maslou); active personality in the process of maturity, the ability to identify their own initiative (L. Phillips); the formation of an adequate self-esteem (A. Bandura), a decisive role as a factor of social environment of the individual psyche and its relations with the outside world (A. Kardiner), the presence of social activity of the individual, its entry into the social experience in social situations (J. Meade).